UJI PERBANDINGAN KOMPOSISI KERTAS DAUR ULANG BERBAHAN DASAR SAMPAH ORGANIK DAN ANORGANIK (Comparative Test of Recycled Paper Composition Made from Organic and inorganic Waste) - Indri Tamara Pulungan; Riswanti Sigalingging; Saipul Bahri Daulay (Universitas Sumatera Utara, 2018)
ABSTRACT The amount of waste in Indonesia is increasing every year, especially paper and plastic waste. Therefore, special handling is needed to reduce the amount of waste produced. The paper production from organic and inorganic waste is an ideal way to overcome the problem. This research aimed to determine the appropriate composition of raw materials in the processing of recycled paper using leaf, plastic and paper waste as materials. This study was conducted in March to July 2017 at the Agricultural Engineering Laboratory, Faculty of Agriculture, Universitas Sumatera Utara and the testing of tensile strength, water absorbency and tearing resistance was done at the Large Hall of Pulp and Paper, Bandung. The method used was an entirely randomized design with 2 factors which were the differences in composition and the type of leaf. The parameters observed were gramature, tensile strength, water absorbency, and tearing resistance. The result showed that the waste composition influenced on the gramature, tensile strength, water absorbency, and tearing resistance. Paper produced was categorized as art paper with the best result was KPS2 i.e 65% paper waste, 5% plastic waste, and 30% mustard with 480 g/m2 gramature value, 2.77 kN/m tensile strength value, 486.7 g/m2 water absorbency value, and >1600 mN tearing resistance value. Keywords: Paper Waste, Plastic Waste, Art Paper. ABSTRAK Jumlah sampah di Indonesia selalu meningkat setiap tahun, khususnya sampah kertas dan sampah plastik. Oleh karena itu, dibutuhkan penanganan khusus agar dapat mengurangi jumlah sampah yang terproduksi. Pembuatan kertas daur ulang menggunakan sampah organik dan anorganik merupakan cara yang ideal untuk menangani masalah tersebut. Penelitian ini bertujuan untuk mengetahui perbandingan komposisi yang tepat dalam pembuatan kertas daur ulang berbahan dasar sampah kertas, sampah daun dan sampah plastik. Penelitian ini dilakukan pada bulan Maret 2017 hingga Juli 2017 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara dan pengujian dilakukan di Balai Besar Pulp dan Kertas, Bandung. Metode penelitian yang digunakan adalah rancangan acak lengkap dengan 2 faktor yaitu perbandingan komposisi dan perbedaan jenis daun. Parameter yang diamati adalah gramatur, ketahanan tarik, ketahanan sobek, dan daya serap air. Hasil penelitian menunjukkan bahwa komposisi sampah kertas memberikan pengaruh berbeda sangat nyata terhadap gramatur, ketahanan tarik dan daya serap air kertas. Kertas yang dihasilkan dapat dikategorikan sebagai kertas seni dengan hasil terbaik ialah KPS2 yang menggunakan 65% sampah kertas, 5% sampah plastik dan 30% sawi dengan nilai gramatur 480 g/m2, ketahanan tarik 2,77 kN/m, daya serap air 486,7 g/m2, dan nilai ketahanan sobek >1600 mN. Kata Kunci: Sampah Kertas, Sampah Plastik, Kertas Seni.